How Does Behavioural Activation Work? A Systematic Review of the Evidence on Potential Mediators - Noortje P. Janssen; Gert‐Jan Hendriks; Céline T. Baranelli; Peter Lucassen; Richard C. Oude Voshaar; Jan Spijker; Marcus J. H. Huibers (2020)
Introduction: Behavioural activation is an effective treatment for depression, but little is known about its working mechanisms. Theoretically, its effect is thought to rely on an interplay between activation and environmental reward. Objective: The present systematic review examines the mediators of behavioural activation for depression. Methods: A systematic literature search without time restrictions in Medline, EMBASE, PsycINFO, The Cochrane Library, and CINAHL resulted in 14 relevant controlled and uncontrolled prospective treatment studies that also performed formal mediation analyses to investigate their working mechanisms. After categorising the mediators investigated, we systematically compared the studies’ methodological quality and performed a narrative synthesis of the findings. Results: Most studies focused on activation or environmental reward, with 21 different mediators being investigated using questionnaires that focused on psychological processes or beliefs. The evidence for both activation and environmental reward as mediators was weak. Conclusions: Non-significant results, poor methodological quality of some of the studies, and differences in questionnaires employed precluded any firm conclusions as to the significance of any of the mediators. Future research should exploit knowledge from fundamental research, such as reward motivation from neurobiology. Furthermore, the use of experience sampling methods and idiographic analyses in bigger samples is recommended to investigate potential causal pathways in individual patients.